GIS dan Pengaduan Perlengkapan Jalan Raya (SIGRA) DISHUB Kabupaten Tegal - Husni Faqih; Zanuar Rifai; Hilda Faiqoturrohmah (Evolusi : Jurnal Sains dan Manajemen, 2020)
Abstract:The Department of Transportation (DISHUB) of Tegal Regency as the organizer of the highway has difficulties in monitoring road equipment due to the small number of personnel with a fairly large work area. Complaints by the public regarding maintenance of road equipment such as lacking or damaged road equipment are needed by DISHUB as input to be more effective and quick in collecting road equipment data. The main objective of this research is to create alternative solutions that can help DISHUB in maintaining road equipment. Data collection techniques by observation, interview, and literature study. The Extreme Programming method is used as a software development method. The results of this research are the Geographical Information System of the Highway that can be utilized by DISHUB of Tegal Regency and the general public who can provide information on the location of road equipment, as well as road equipment complaints services. Keywords:GIS; Geographic Information System; Extreme Programming